PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT. X SURABAYA - Adellia Prasetyo Dewayanti; Rini Nurahaju; Gartinia Nurcholis (Jurnal Psikologi Poseidon, 2023)
Employee performance is a very important part, because it is evident that every company wants employees to work seriously according to their abilities to achieve good work results. The purpose of this study was to determine the influence of leadership on employee performance at PT. X Surabaya, the effect of job satisfaction on employee performance at PT. X Surabaya, and the influence of leadership and job satisfaction together on employee performance at PT. X Surabaya. This study uses a quantitative approach to the type of causality research and data collection in the form of a survey. The psychological measurement tool uses 3 scales, namely the employee performance scale, the leadership scale and the job satisfaction scale. The population in this study amounted to 85 employees. The sampling technique in this study was non-probability sampling using saturated sampling techniques. The results of this study indicate that 1) there is an influence of leadership on employee performance at PT. X Surabaya by contributing 49.5%. 2) there is an effect of job satisfaction on employee performance at PT. X Surabaya by contributing 48.2%. 3) there is an influence of leadership and job satisfaction together on employee performance by contributing 58.2%.